Pengembangan LKPD Berbasis Etnofotografi Mandailing pada Materi Kearifan Lokal KelaS V SD/MI - Rizki Adawiah Lubis; Rahmi Seri Hanida; Suryadi Nasution (Pendekar: Jurnal Pendidikan Berkarakter, 2026)
Abstract: Integrating local culture into the learning process is essential to enhance the relevance of instructional materials to students' experiences while supporting the preservation of local wisdom. However, the availability of teaching materials that incorporate Mandailing cultural contexts remains limited, particularly in science and social studies (IPAS) learning at the elementary school level. This study aimed to develop a Mandailing ethnophotography-based Student Worksheet (LKPD) on local wisdom materials for fifth-grade elementary school students. This study employed a Research and Development (R&D) approach by adapting the Borg and Gall model. The research instruments consisted of material expert validation sheets, ethnophotography expert validation sheets, and student readability questionnaires. Data were analyzed using descriptive quantitative techniques through percentage calculations to determine the validity and practicality levels of the developed product. The results indicated that the developed LKPD achieved a validity score of 87% from material experts and 75% from ethnophotography experts, both categorized as valid. Furthermore, the readability test involving 29 students obtained a score of 88%, which was classified as highly practical. The LKPD incorporates contextual and interactive learning activities, including visual observation of local culture, group discussions, narrative writing, and the illustration of Mandailing cultural elements. The Mandailing ethnophotography-based LKPD is valid and highly practical for use in elementary school IPAS learning. The implementation of this worksheet not only supports the achievement of learning objectives but also contributes to fostering students’ awareness, appreciation, and pride in the local cultural heritage of the Mandailing community.Abstrak: Pembelajaran yang mengintegrasikan budaya lokal menjadi penting untuk meningkatkan relevansi materi dengan pengalaman peserta didik sekaligus mendukung pelestarian kearifan lokal. Namun, ketersediaan bahan ajar yang mengakomodasi konteks budaya Mandailing masih terbatas, khususnya pada pembelajaran IPAS di sekolah dasar. Penelitian ini bertujuan untuk mengembangkan Lembar Kerja Peserta Didik (LKPD) berbasis etnofotografi Mandailing pada materi kearifan lokal untuk peserta didik kelas V Sekolah Dasar. Penelitian ini menggunakan metode Research and Development (R&D) dengan mengadaptasi model Borg and Gall. Instrumen penelitian yang digunakan meliputi lembar validasi ahli materi, lembar validasi ahli etnofotografi, dan angket uji keterbacaan peserta didik. Data dianalisis menggunakan teknik analisis deskriptif kuantitatif berupa perhitungan persentase untuk menentukan tingkat kevalidan dan kepraktisan produk yang dikembangkan Hasil penelitian menunjukkan bahwa LKPD yang dikembangkan memperoleh tingkat kevalidan sebesar 87% dari ahli materi dan 75% dari ahli etnofotografi, yang keduanya termasuk dalam kategori valid. Selain itu, hasil uji keterbacaan yang melibatkan 29 peserta didik memperoleh skor sebesar 88% dengan kategori sangat praktis. LKPD ini memuat aktivitas pembelajaran yang kontekstual dan interaktif, seperti pengamatan visual budaya lokal, diskusi kelompok, penulisan narasi, dan penggambaran unsur budaya Mandailing. LKPD berbasis etnofotografi Mandailing yang dikembangkan valid dan sangat praktis untuk digunakan dalam pembelajaran IPAS di sekolah dasar. Penggunaan LKPD ini tidak hanya mendukung pencapaian tujuan pembelajaran, tetapi juga berkontribusi dalam menumbuhkan kepedulian, apresiasi, dan kebanggaan peserta didik terhadap warisan budaya lokal Mandailing.